Laboratory evaluation of selected disinfectants on gumboro disease virus - Bayoumie, H. A. A.; Mohamed, I. A. A. (2009)
The efficacy of iodine and glutraldehyde containing compounds against infectious bursal disease virus (rnDV) was assayed by comparing the virus titer before and after exposure to each disinfectant. The test was conducted at room temperature in presence or absence of organic matter "40% foetal bovine serum".
Includes reference.
Summary in Arabic.
Keywords: Chickens -- Diseases -- Control; Chickens -- Virus diseases; Disinfection and disinfectants